The Effect of Using X for News on Political Participation Online and its Impact on Political Participation Offline - Naura Nadhira Syahfiraputri; Kunto Adi Wibowo; Detta Rahmawan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to look at the influence of using social media platform X, as a social media platform with 25 million users in Indonesia, for news on political participation online and its impact on political participation offline among active university students in West Java. This research refers to quantitative research methods and managed to get 180 respondents through distributing questionnaires with Google Form using the 5-point Likert scale method. From the results of the research with 180 respondents, 45 respondents were male and 135 were female who were active students from 13 universities in West Java. Other research results also produced a good validity test (Rcount>Rtable), a reliable reliability test (Cronbach's Alpha> 0.60), and regression analysis with path analysis test. The results of this study indicate that there is an effect of using X for news on political participation online and its impact on the political participation offline of students in West Java. However, the influence of using X for news found on political participation offline through political participation online is an indirect influence.